2019
DOI: 10.1159/000493988
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Ambulatory Urodynamics in the Evaluation of Treatment Effect of Sacral Neuromodulation

Abstract: Objectives: To assess the improvement of symptoms by sacral neuromodulation (SNM) in an objective way by carrying out an ambulatory urodynamic study (ambulatory-UDS). Until now, successful treatment has been defined as a ≥50% improvement recorded on voiding diaries. Voiding diaries are a patient reported outcome tool. A tool with less bias is desired to evaluate the treatment results before an expensive permanent system is implanted. Methods: Between 2002 and 2015, a total of 334 patients with lower urinary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Rademakers et al [13] have shown aUDS to be particularly useful in determining true acontractility and DO, and assigning a UDS cause for UI of unknown cause. Drossaerts et al have also shown that aUDS is a valuable tool when assessing the effectiveness of sacral neuromodulation in patients with LUTS [14]. Likewise, we found aUDS particularly useful in diagnosing detrusor overactivity, stress urinary incontinence, and sensory urgency.…”
Section: Clam Cystoplastysupporting
confidence: 75%
“…Rademakers et al [13] have shown aUDS to be particularly useful in determining true acontractility and DO, and assigning a UDS cause for UI of unknown cause. Drossaerts et al have also shown that aUDS is a valuable tool when assessing the effectiveness of sacral neuromodulation in patients with LUTS [14]. Likewise, we found aUDS particularly useful in diagnosing detrusor overactivity, stress urinary incontinence, and sensory urgency.…”
Section: Clam Cystoplastysupporting
confidence: 75%
“…UDS is widely used for patients with suspected neurogenic lower urinary tract disturbance (NLUTD) [1]. There are several issues as to UDS and NLUTD [2, 3]. Some patients have symptomatic post-UDS infectious complications, especially urinary tract infection (UTI), partly due to chronic bacteriuria, pyuria, or nonspecific inflammation caused by the patients’ immune status and bacterial status, including bacterial numbers or virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas inability to void during PFS should not be confused with acontractility of the detrusor the WG prefers the descriptive term "situational inability to void" (see part 1) and does not recommend the terms paruresis, shy bladder syndrome or bashful bladder syndrome, because they are not precisely defined at present and demarcations from somatic or pharmacogenic dysfunctions are insufficiently established. 37 In this context, the WG also does not recommend the term "nonobstructive urinary retention" for patients unable to void during UDS (or "chronic nonobstructive urinary retention" as a syndrome) as is frequently referred to in relation to neuromodulation (e.g., 38 for the simple fact that it is impossible to diagnose (absence of) BOO or low UR, without a PFS voiding, when retention exists. The WG also recommends considering that 'situational inability to void as usual' 2,4 i.e., not representative voiding, will often negatively affect the pressure-flow ratio and quantifications of DVC and UR (or BOO) and may lead to over-diagnosis of outlet and/or DVC function abnormalities.…”
Section: Acontractile Detrusor and Inability To Voidmentioning
confidence: 99%